2017
DOI: 10.1111/1748-5967.12218
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome of the black‐tailed hornet, Vespa ducalis (Hymenoptera: Vespidae): Genomic comparisons in Vespoidea

Abstract: We sequenced the complete mitochondrial genome (mitogenome) of the black‐tailed hornet, Vespa ducalis (Hymenoptera: Vespidae). The genome was 15,779‐bp long and contained typical sets of genes [13 protein‐coding genes (PCGs), 22 tRNAs, and 2 rRNAs]. The V. ducalis A + T‐rich region was 166‐bp long and was the shortest of all sequenced Vespoidea genomes, including Vespa. The genome was highly biased toward A/T nucleotides—80.1 % in the whole genome, 77.8 % in PCGs, 83.4–85.6 % in RNAs, and 92.8 % in the A + T‐r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
2
5
0
Order By: Relevance
“…Polistinae forms a sister relationship with Vespinae, which is supported by previous studies on both morphological characteristics and molecular data [22,60,61]. In addition, within the subfamily Polistinae, the relationship (Ropalidia + Parapolybia) is concordant with previous morphological analysis of Polistinae that the two genera belong to one tribe [4,21].…”
Section: Phylogenetic Relationships and Divergence Time Estimationsupporting
confidence: 86%
“…Polistinae forms a sister relationship with Vespinae, which is supported by previous studies on both morphological characteristics and molecular data [22,60,61]. In addition, within the subfamily Polistinae, the relationship (Ropalidia + Parapolybia) is concordant with previous morphological analysis of Polistinae that the two genera belong to one tribe [4,21].…”
Section: Phylogenetic Relationships and Divergence Time Estimationsupporting
confidence: 86%
“… 2017 ; Kim et al. 2017a , 2017b ; Takahashi et al. 2017 ) was shown to be similar to the result by the combined analysis based on 45 morphological characters and six genes (Perrard et al.…”
supporting
confidence: 79%
“…Phylogenetic analysis using the 13 mitochondrial proteincoding genes from 11 closely related taxa of Vespidae (Cameron et al 2008;Chen et al 2016;Song et al 2016;Wei et al 2016;Zhou et al 2016;Fan et al 2017;Haddad et al 2017;Kim et al 2017aKim et al , 2017bTakahashi et al 2017) was shown to be similar to the result by the combined analysis based on 45 morphological characters and six genes (Perrard et al 2013) (Figure 1). Although more high resolution sequence data from more species may help resolve these differences.…”
mentioning
confidence: 58%
“…Previous studies support these findings, the phylogenetic analysis based on 45 morphological characters and molecular analysis showed the presence of close relationships between V. mandarinia and V. ducalis while the other three Vespa species were placed in different groups (Perrard et al, 2013). Based on the nucleotide sequences of the 13 protein-coding genes, close relationships between V. mandarinia, V. ducalis and V. affinis, were found (Okuyama et al, 2017;Takahashi et al, 2018), and between V. mandarinia and V. ducalis (Kim et al, 2017;Zhang, Huang, Chen & Li, 2018). On the contrary with the current study, a close relationship was found between V. mandarinia and V. orientalis based on the un-gapped sequences of a multiple sequence alignment (Haddad et al, 2017), while V. orientalis and V. velutina were placed in close groups based on the nucleotide sequences of the 13 protein-coding genes (Takahashi et al, 2018).…”
Section: Phylogenetic Treementioning
confidence: 54%
“…The mtDNA of some Vespa species have been sequenced including: V. mandarinia (Chen, Wei, & Liu, 2016), V. orientalis (Haddad et al, 2017), V. affinis (Okuyama, Martin, & Takahashi, 2017), V. ducalis (Kim, Jeong, Jeong, Kim, & Kim, 2017), and V. velutina (Takahashi, Okuyama, Minoshima, & Takahashi, 2018). The phylogenetic relationships between Vespa have been studied based on morphological characters (Perrard, Pickett, Villemant, Kojima, & Carpenter, 2013) while few studies have focused on the genetic characteristics of these hornets.…”
Section: Introductionmentioning
confidence: 99%